2017
DOI: 10.1515/mper-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli of Collaboration in Product Development: A Case Study in a Project Manufacturing Company

Abstract: Accepted: 8 November 2017There is already a wide acceptance on the importance of involving supplier and customer companies in product development. Decent understanding prevails on the relationshiporiented approach to product development including various collaboration forms. However, there is less research on the factors explaining the decision of attending to joint product development. In addition, less studies have examined the integrated role of both suppliers and customers in product development initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Regardless of the number of case studies reported in papers, an average of 29 interviews forms the basis of these although some build on a very large number of interviews, for example "over 100" in one longitudinal case study (Åberg and Bengtson, 2015). Many papers also use workshops to complement other sources of empirical data (Jääskeläinen et al;Wynstra et al, 2003).…”
Section: Methods and Analysis: Focus On Surveys And Case Studiesmentioning
confidence: 99%
“…Regardless of the number of case studies reported in papers, an average of 29 interviews forms the basis of these although some build on a very large number of interviews, for example "over 100" in one longitudinal case study (Åberg and Bengtson, 2015). Many papers also use workshops to complement other sources of empirical data (Jääskeläinen et al;Wynstra et al, 2003).…”
Section: Methods and Analysis: Focus On Surveys And Case Studiesmentioning
confidence: 99%
“…They proposed a requirement management model that assures transparency on the customers' constraints and the downstream constraints coming from engineering, production and supply. Jääskeläinen et al (2017) proposed a method to make customers and suppliers more involved in the NPD process; whereas, Tiedemann et al (2019) proposed an NPD process portfolio model to support the organisation of mixed standard and custom products within ETO realities, triggering new interesting directions for ETO NPD literature. Concerning the effective use of knowledge and the knowledge protection in the knowledge-intensive ETO context, Galati et al (2019) explored the relationship between defensive mechanisms and the need to balance knowledge sharing and protection.…”
Section: New Product Development Portfolio and Capabilitiesmentioning
confidence: 99%